Penerapan Program Literasi dalam Menumbuhkan Minat Baca Siswa melalui Teknik AIH (Studi Kasus pada Kelas IV SDN Cinangka 03 Kabupaten Bandung) - Salsa Berliana Putri; Agil Nanggala (Departement of Mathematics Education, 2023)
The purpose of this study is to describe the application of literacy with the AIH technique (reasons, content and wisdom) to foster interest in reading in elementary school students. The approach used in this research article is a qualitative approach with case studies through data collection methods based on interviews, observation and documentation. The data analysis technique for this research is data reduction, data presentation, and drawing conclusions. The results of this study prove that the class teacher has used the concept of a culture of reviewing books or reading using the AIH method and proving that this method is suitable for application at the elementary education level to increase students' interest in reading. And this concept matches the level of early literacy and basic literacy in students.